Perencanaan Pemanfaatan Potensi Lokal dalam Membangun Desa Wisata dengan Pendekatan Konsep Community Based Tourism (CBT) di Desa Bumi Rahayu - Budiarti, Ika Niswatin; Imelda, Dewi Qomariah; Soimah, Nurus; Alfiansyah, Muhammad (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
This activity aims to mobilize community participation in planning and utilizing the local potential of Bumi Rahayu Village to develop a Tourism Village. Through the Community Based Tourism (CBT) concept approach, it is hoped that it can strengthen the involvement of local communities in destination management, improve the welfare of local communities, and preserve culture and the environment. The methodology in this service is to provide knowledge and understanding of the potential of villages and tourist villages using discussion methods, field surveys and creating tourism concepts. This activity produces an overview of the tourism concept of the Bumi Rahayu river flow by optimizing the natural wealth around it. The description given focuses on land use to increase tourist attraction, such as the placement of entrance gates, parking locations,